Molecular and biochemical responses of hypoxia exposure in Atlantic croaker collected from hypoxic regions in the northern Gulf of Mexico. - Md Saydur Rahman; Peter Thomas (PLoS ONE)
A major impact of global climate change has been the marked increase worldwide in the incidence of coastal hypoxia (dissolved oxygen, DO<2.0 mg l-1). However, the extent of hypoxia exposure to motile animals such as fish collected from hypoxic waters as well as their molecular and physiological responses to environmental hypoxia exposure are largely unknown. A suite of potential hypoxia exposure biomarkers was evaluated in Atlantic croaker collected from hypoxic and normoxic regions in the northern Gulf of Mexico (nGOM), and in croaker after laboratory exposure to hypoxia (DO: 1.7 mg l-1). Expression of hypoxia-inducible factor-α, hif-α; neuronal nitric oxide synthase, nNOS; and insulin-like growth factor binding protein, igfbp mRNAs and protein carbonyl (PC, an oxidative stress indicator) content were elevated several-fold in brain and liver tissues of croaker collected from nGOM hypoxic sites. All of these molecular and biochemical biomarkers were also upregulated ~3-10-fold in croaker brain and liver tissues within 1-2 days of hypoxia exposure in controlled laboratory experiments. These results suggest that hif-αs, nNOS and igfbp-1 transcripts and PC contents are useful biomarkers of environmental hypoxia exposure and some of its physiological effects, making them important components for improved assessments of long-term impacts of environmental hypoxia on fish populations.